2003
DOI: 10.1677/erc.0.0100131
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin D and retinoids in controlling prostate cancer progression.

Abstract: Prostate cancer is a leading cause of cancer-related deaths in many countries. Premalignant lesions and invasive cancer occur more frequently in the prostate than in any organ other than the skin. Yet, the incidence of clinically detected prostate cancer is much lower than the histopathological incidence. The slow growth of prostate cancer and the low incidence of clinically manifest disease in some geographical locations or racial/ethnic groups suggest that prostate cancer can be controlled, perhaps by dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 64 publications
0
34
0
1
Order By: Relevance
“…Since mice lacking both RXRb and RXRg are normal in terms of prostate morphology and function (Krezel et al 1996), and considering that the active RA receptor is mostly a heterodimer of one RAR and one RXR , the critical RXR in prostate biology appears to be RXRa. Moreover, to mediate multiple signaling pathways in the prostate, RXRa may also partner with other nuclear receptors, such as peroxisome proliferator-activated receptor g and vitamin D receptor, whose ligands have been shown to inhibit prostate cancer cell growth (Kubota et al 1998, Peehl & Feldman 2003. The human chromosomal region, 9q34.3, in which RXRa gene is mapped, is characterized by a high rate of recombination (Almasan et al 1994), and the incidence of loss of heterozygosity at this locus has been reported to be 20% in prostate cancer (Ruijter et al 1999).…”
Section: Rxramentioning
confidence: 99%
“…Since mice lacking both RXRb and RXRg are normal in terms of prostate morphology and function (Krezel et al 1996), and considering that the active RA receptor is mostly a heterodimer of one RAR and one RXR , the critical RXR in prostate biology appears to be RXRa. Moreover, to mediate multiple signaling pathways in the prostate, RXRa may also partner with other nuclear receptors, such as peroxisome proliferator-activated receptor g and vitamin D receptor, whose ligands have been shown to inhibit prostate cancer cell growth (Kubota et al 1998, Peehl & Feldman 2003. The human chromosomal region, 9q34.3, in which RXRa gene is mapped, is characterized by a high rate of recombination (Almasan et al 1994), and the incidence of loss of heterozygosity at this locus has been reported to be 20% in prostate cancer (Ruijter et al 1999).…”
Section: Rxramentioning
confidence: 99%
“…2 This finding is very interesting and important in that it may provide an explanation for a number of puzzling and inconsistent results from studies investigating the links between prostate cancer, solar UVB radiation (280 -315 nm) and vitamin D. While there is considerable observational epidemiologic and in vitro evidence that UVB and/or vitamin D reduce the risk of prostate cancer, 1,3,4 there are also a number of reports of no risk reduction with UVB and vitamin D. 1 While some of the effect reported by Tuohimaa et al 1 may be due to the negative effects of vitamin A (retinol) 5 found in fish liver oil, which is a major source of vitamin D in Norway, 1 this may not explain all of the increased risk of prostate cancer for higher values of 25(OH)-vitamin D 3 .…”
Section: Dear Sirmentioning
confidence: 99%
“…The observation that 1,25D prevents proliferation of prostate cancer cells (Peehl & Feldman 2003) has attracted considerable interest because of the possibility of using vitamin D based therapies for prostate cancer (Chen et al 2000. A deficiency of CYP27B1 enzyme activity levels was noted in prostate cancer cells compared with normal cells ) and this correlated with the inability of exogenous 25D to inhibit cellular proliferation presumably because of insufficient local 1,25D production by CYP27B1 .…”
Section: Discussionmentioning
confidence: 99%